QsvR represses the transcription of polar flagellum genes in Vibrio parahaemolyticus. (January 2023) - Zhang, Miaomiao; Xue, Xingfan; Li, Xue; Luo, Xi; Wu, Qimin; Zhang, Tingting; Yang, Wenhui; Hu, Lingfei; Zhou, Dongsheng; Lu, Renfei; Zhang, Yiquan
Abstract: Vibrio parahaemolyticus produces dual flagellar systems, i.e., the sheathed polar flagellum (Pof) and numerous lateral flagella (Laf), both of which are strictly regulated by numerous factors. QsvR is an AraC-type regulator that controls biofilm formation and virulence of V. parahaemolyticus . In the present study, we showed that deletion of qsvR significantly enhanced swimming motility of V. parahaemolyticus, while the swarming motility was not affected by QsvR. QsvR bound to the regulatory DNA regions of flgAMN and flgMN within the Pof gene loci to repress their transcription, whereas it negatively controls the transcription of flgBCDEFGHIJ and flgKL-flaC in an indirect manner. However, over-produced QsvR was also likely to possess the binding activity to the regulatory DNA regions of flgBCDEFGHIJ and flgKL-flaC in a heterologous host. In summary, this work demonstrated that QsvR negatively regulated the swimming motility of V. parahaemolyticus via directly action on the transcription of Pof genes. Highlights: QsvR repressed the swimming motility of V. parahaemolyticus. QsvR directly repressed the transcription of flgAMN and flgMN. QsvR indirectly repressed the transcription of flgBCDEFGHIJ and flgKL-flaC.